Pemikiran Mohammed Ayoob Mengenai Multidimensionalitas Politik Islam Modern di Negara Islam Hingga ke Negeri Muslim (Indonesia) - Mutholingah, Siti (Proceedings of Annual Conference for Muslim Scholars, 2019)
Politics is something that is urgent in Islamic studies both in Islamic countries and in Muslim countries like Indonesia. The aim of the study is to analyze the thoughts of Mohammed Ayoob who offer the concept of modern Islamic politics and be multidimensional in nature. This study is a literature study with the main source is a book by Mohammed Ayoob entitled "The Many Faces of Political Islam: Religion and Politics in the Muslim World". The results of this study are: (1) The concept of modern Islamic politics as a complex, continuous and change political ideology; (2) Islamic political multidimensionality includes: self-proclaimed Islamic countries (Saudi Arabia and Iran), sources of Islamist ideology and activism (Egypt and Pakistan), democratic Muslim majority countries (Turkey and Indonesia), national Islamist resistance movements (Hamas and Hezbollah) and trans-national Islamic organizations (Jamaat Tablighi, Hizb at-Tahrir, and al-Qaeda). This multidimensionality of Islamic politics proves that political Islam does not have the same shape and structure throughout the Muslim world.